The Use of Negative Pressure with Instillation and Dwell for the Treatment of Necrotizing Fasciitis - Reider, Kersten (Cureus, 2018)
The human body is a complex, multisystem organism that can manifest disease processes in a multitude of ways. Over the decades, technological advancements have allowed us to make precise diagnoses so that clinicians can thoroughly treat the underlying cause. Frequently these disease processes require surgical intervention to eliminate the progression and provide the patient with positive outcomes. When surgical intervention is required, the patient is often left with large complex wounds. Just like medical advancements, wound care modalities have made vast technological improvements. Wounds previously being treated with simple but labor-intensive treatments such as gauze packings and return operating room interventions, can now be treated with negative pressure wound therapy combined with instillation and dwell (NPWTi-d). This therapy combines the benefits of negative pressure while cleansing the wound through the instillation of a topical wound cleanser in a controlled environment. In this case review, we will highlight a case of necrotizing fasciitis in which surgical intervention was required and negative pressure wound therapy with instillation and the use of reticulated open cell foam dressing with through holes (ROCF-CC) was utilized. Negative pressure with instillation was used to remove infectious material and other nonviable tissue from the wound base while promoting granulation tissue production. By utilizing this treatment, we were able to decrease the patient's return trips to the operating room (OR), enhance granulation tissue production, and ultimately achieve positive patient outcomes.